Engineering innovative products a practical experience - Woods, Roger 1963-; Raerty, Karen; Hermon, John Paul; Murphy, Julian 1980- (Wiley, 2014)
Engineering Innovative Products: A Practical Experience is a pioneering book that will be of key use to senior undergraduate and graduate engineering students who are being encouraged to explore innovation and commercialization as part of their courses. The book will teach the essential skills of entrepreneurship and address the fundamental requirements needed to establish a successful technology company.